2020
DOI: 10.1016/j.bbi.2019.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tissue-nonspecific alkaline phosphatase (TNAP) enzyme activity in cerebral microvessels is coupled to persistent neuroinflammation and behavioral deficits in late sepsis

Abstract: Sepsis is a host response to systemic inflammation and infection that may lead to multi-organ dysfunction and eventual death. While acute brain dysfunction is common among all sepsis patients, chronic neurological impairment is prevalent among sepsis survivors. The brain microvasculature has emerged as a major determinant of sepsis-associated brain dysfunction, yet the mechanisms that underlie its associated neuroimmune perturbations and behavioral deficits are not well understood. An emerging body of data sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 79 publications
3
24
0
Order By: Relevance
“…Mice were deeply anesthetized with isoflurane and transcardially perfused (Masterflex 7524-10, Cole-Parmer, Vernon Hills, IL) as described previously [19]. Briefly, blood was removed with 0.9% saline followed by perfusion and fixation with 4% chilled paraformaldehyde (PFA, Fisher Scientific, Pittsburgh, PA).…”
Section: Tissue Collecting and Processingmentioning
confidence: 99%
“…Mice were deeply anesthetized with isoflurane and transcardially perfused (Masterflex 7524-10, Cole-Parmer, Vernon Hills, IL) as described previously [19]. Briefly, blood was removed with 0.9% saline followed by perfusion and fixation with 4% chilled paraformaldehyde (PFA, Fisher Scientific, Pittsburgh, PA).…”
Section: Tissue Collecting and Processingmentioning
confidence: 99%
“…Mouse brains were analyzed as free-floating sections to localize immunoreactivity for GFAP (Z0334, Dako/Agilent; 1:10,000 primary, 1:10,000 secondary), Iba-1 (019-19741, Wako; 1:2,000 primary, 1:1,000 secondary), ALPL (702454, Invitrogen, 1:100 primary, 1:1,000 secondary), and CD11b (ab 133357 Abcam, 1:500 primary, 1:1,000 secondary) using a modified ABC procedure (Vector Laboratories, Burlingame, CA) as previously described [28,29]. Briefly, sections were treated to remove endogenous peroxidases followed by permeabilization.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In an elegant in vitro experiment, it was demonstrated that an experimental cytokine mixture, which mimicked plasma obtained from patients with severe sepsis, led to enhanced human leukocytes adhesion to human cerebrovascular endothelial cells (hCMEC/D3) [ 42 ]. Similarly, increased leukocyte and platelet adhesion to cerebral vessels is a common finding in animal models of SAE [ 43 47 ]. Corroborating those results, we observed sepsis increased both leukocyte and platelet adhesion to pial vessels of mice.…”
Section: Discussionmentioning
confidence: 99%